Sourcing the Neronia: Tacitus, Annals 14.20–1 - Woodman, A. J. (Histos, 2022)
This paper suggests that the contemporary reception of the Neronia as described by Tacitus in the Annals is indebted to the Roman reception of rhetoric as described by Suetonius in his De grammaticis et rhetoribus.